2003
DOI: 10.1677/jme.0.0310083
|View full text |Cite
|
Sign up to set email alerts
|

Steroids control the aromatase gene expression in purified germ cells from the adult male rat

Abstract: The ability of the testis to convert irreversibly androgens into estrogens is related to the presence of a microsomal enzymatic complex named aromatase. In rodents, germ cell production of estrogens is known, although the regulation of the cytochrome P450 aromatase (P450 arom) gene expression is not completely elucidated. In the present study, we have investigated the putative effects of steroids (testosterone, 5α-dihydrotestosterone (DHT) and estradiol) on Cyp19 gene expression in purified adult rat pachytene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 59 publications
1
16
0
1
Order By: Relevance
“…The long-lasting lower level of estradiol did not affect the immunolocalization of P450 aromatase in germ cells, however, at the same time, the P450 aromatase immunoreactivity was lower. In vitro studies showed that both testosterone and dihydrotestosterone (DHT) stimulated the expression of the P450arom gene and the aromatase activity in pachytene spermatocytes and round spermatids, while estradiol down-regulated the aromatase transcription in germ cells [41]. Additionally, we detected the presence of P450arom in the cytoplasm of sloughed immature germ cells in the lumen of seminiferous tubules in testes of experimental rats.…”
Section: Discussionmentioning
confidence: 75%
“…The long-lasting lower level of estradiol did not affect the immunolocalization of P450 aromatase in germ cells, however, at the same time, the P450 aromatase immunoreactivity was lower. In vitro studies showed that both testosterone and dihydrotestosterone (DHT) stimulated the expression of the P450arom gene and the aromatase activity in pachytene spermatocytes and round spermatids, while estradiol down-regulated the aromatase transcription in germ cells [41]. Additionally, we detected the presence of P450arom in the cytoplasm of sloughed immature germ cells in the lumen of seminiferous tubules in testes of experimental rats.…”
Section: Discussionmentioning
confidence: 75%
“…4). In addition, we have shown that androgens and estrogens exert oppsite effects on aromatase gene expression [28,29]. It is noteworthy that the effect of TNF␣ is amplified in presence of dexamethasone (not shown) which is may be supported by the presence of another promoter as shown in adipose tissue [30].…”
Section: Role Of Aromatase/estrogens In Male Reproductionmentioning
confidence: 76%
“…TGF␤, transforming growth factor beta; TNF␣, tumor necrosis factor alpha; cAMP, cyclic AMP; PS, pachytene spermatocyes and RS, round spermatids. The testicular cells were incubated with these factors then the amount of specific P450arom transcripts and the production of estradiol were determined as described previously [19,28,29].…”
Section: Role Of Aromatase/estrogens In Male Reproductionmentioning
confidence: 99%
“…Gene transcription, resulting from estrogen binding to their cognate receptors, is one way in which local concentrations of estrogens may be regulated (Bourguiba et al 2003;Harada et al 1993;Iivonen et al 2006;Ishunina et al 2007;Roselli et al 1987;Yilmaz et al 2009;Zhao et al 2008). In this context, it is of note that aromatase mRNA may be either downregulated or upregulated in response to estradiol.…”
Section: Regulation Of Hippocampal Estradiol Synthesismentioning
confidence: 99%